A tale of two cities - Dickens, Charles (Penguin Random House UK. London, 2016)
A Tale of Two Cities is a historical novel set during the turbulent times of the French Revolution, focusing on the cities of London and Paris. The story follows Charles Darnay, a French aristocrat, and Sydney Carton, a disillusioned English lawyer, whose lives intertwine with that of Lucie Manette, a young woman whose father has been unjustly imprisoned. The novel explores themes of sacrifice, justice, and resurrection, as characters confront the brutality of revolution and the possibility of personal redemption. Dickens masterfully contrasts the chaos and violence in France with the relative calm of England, creating a vivid picture of the era$1 (Bs social and political upheaval.s